“Integrating Digital Technologies in Extracurricular Activities to Enhance Students’ Innovative Skills” - Djabbarova Nargiza Bakitovna (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores the integration of digital technologies in school extracurricular activities and their impact on enhancing students’ innovative skills. The study emphasizes the role of interactive digital tools, online platforms, and multimedia resources in fostering creativity, critical thinking, and problem-solving abilities. The paper also discusses pedagogical strategies to maximize engagement and independent learning through technology-enhanced extracurricular programs.